New Record of Fungi Cerotelium malvicola (Speg.) Dietel (Uredinales) Parasitic on Hibiscus Species from Nepal - Adhikari, Mahesh Kumar (Journal of Plant Resources, 2023)
Recently a rust fungi (Uredinales) identified as Cerotelium malvicola (Speg.) Dietel parasitic on Hibiscus species is reported as new addition to fungi of Nepal.